O Dużych Ugięciach Cienkościennego Pasma Sprężystego - Kornecki, A. (Engineering Transactions, 1961)
This paper deals with large deflections of a long, thin elastic plate of a rectangular cross section, loaded by any lateral forces varying along the length of the plate and by constant bending moments acting on the short edges. The long edges of the plate are free. The problem is linearized, and reduces to the evaluation of a complex function of real variables that satisfies a lineary differential equation (2.17) with variable coefficients, and suitable boundary conditions. Some methods of solution of this equation are considered, the methods being based on the linear theory of thin-walled, elastic, shallow shells.